Sensitive and selective method for the analysis of menthol from pharmaceutical products by RP-HPLC with refractive index detector - K A Shaikh; Sachin D Patil (Wolters Kluwer Medknow Publications, 2010)
Objective : Liquid chromatography with refractive index (RI) detection has been found to be very useful for the determination of menthol from pharmaceutical products. A simple and rapid HPLC method has been developed for this purpose compared to conventional GC methods, requiring no special sample pretreatment for the determination of menthol from pharmaceutical products. Materials and Methods : A chromatographic separation was achieved on a Inertsil ODS 3V (4.6mm×250mm, 5μm) column using water : methanol (30:70 v/v) as a mobile phase, at a flow rate of 1.0 ml/min. Results : Method was validated as per ICH guidelines for various parameters such as precision, linearity, accuracy, solution stability, robustness, limit of detection and quantification. Results were found to be within acceptable limits. Conclusion : The method has been successfully applied for the quantification of menthol from syrup formulations. The developed method can be conveniently used by the quality control department to determine assay of menthol from pharmaceutical preparations.